Analysis of formaldehyde content and health risk assessment of commonly consumed fish at three wet markets in Selangor, Malaysia - Abdullah, Siti Aminah (2013)
The health benefits of consuming fish as a source of omega-3 fatty acids have been established. It can reduce cholesterol levels and the incidence of stroke and can protect against cardiovascular disease, improve cognitive development in children and slow cognitive decline in the elderly. Formaldehyde is used as an antibacterial agent and preservative in food processing for dried food, fish, certain oil and fats and disinfectants for container. Formaldehyde is classified by the International Agency for Research on Cancer (IARC) in the Group 1 as carcinogenic to humans. A survey was conducted on adults, adolescents and children to identify the type of commercial fish commonly consumed in order to assess the formaldehyde content and health risks of consuming different type of commercial fish. Based on the survey, seven types of commercial fish species were analysed. All of the samples were purchased in different wet markets and analysed under different circumstances; raw, boiled and fried. Formaldehyde was determined in all fish circumstances analysed using Nash’s reagent and spectrophotometer. The formaldehyde content in the sample was in the range of 2.38 to 2.95 μg/g for raw, 2.08 to 2.35 μg/g for boiled and 2.28 to 2.49 μg/g for fried fish meat. This study showed that formaldehyde content among all fish species and fish circumstances were still lower than the amount set by Malaysian Food Act (1985) and Malaysian Food Regulation (1985) whereby the maximum limit value for formaldehyde in fish and fish products are 5mg/kg. From the risk assessment calculation, there was no adverse health effects from the consumption of fish contain of low formaldehyde. Thus, the fish from wet market can be considered safe for consumption for all age groups.